Gnosticism, Platonism and the late ancient world: essays in honour of John D. Turner - Corrigan, Kevin; Rasimus, Tuomas; Turner, John Douglas (Nag Hammadi and Manichaean studies, 2013)
Part I. Gnosticism and other religious movements of antiquity -- part II. Crossing boundaries : Gnosticism and Platonism